Radial measurements of IMF-sensitive absorption features in two massive ETGs. Issue 1 (14th December 2017) - Vaughan, Sam P; Davies, Roger L; Zieleniewski, Simon; Houghton, Ryan C W
Abstract: We make radial measurements of stellar initial mass function (IMF) sensitive absorption features in the two massive early-type galaxies NGC 1277 and IC 843. Using the Oxford Short Wavelength Integral Field specTrogaph (SWIFT), we obtain resolved measurements of the Na i 0.82 and FeH 0.99 indices, amongst others, finding both galaxies show strong gradients in Na i absorption combined with flat FeH profiles at ∼0.4 Å. We find these measurements may be explained by radial gradients in the IMF, appropriate abundance gradients in [Na/Fe] and [Fe/H], or a combination of the two, and our data are unable to break this degeneracy. We also use full spectral fitting to infer global properties from an integrated spectrum of each object, deriving a unimodal IMF slope consistent with Salpeter in IC 843 ( x = 2.27 ± 0.17) but steeper than Salpeter in NGC 1277 ( x = 2.69 ± 0.11), despite their similar FeH equivalent widths. Independently, we fit the strength of the FeH feature and compare to the E-MILES and CvD12 stellar population libraries, finding agreement between the models. The IMF values derived in this way are in close agreement with those from spectral fitting in NGC 1277 ($x_{CvD}=2.59^{+0.25}_{-0.48}$, $x_{\mathrm{E\text{-}MILES}}=2.77± 0.31$ ), but are less consistent in IC 843, with the IMF derived from FeH alone leading to steeper slopes than when fitting the full spectrum ($x_{CvD}=2.57^{+0.30}_{-0.41}$, $x_{\mathrm{E\text{-}MILES}}=2.72± 0.25$ ). This work highlights the importance of a large wavelength coverage for breaking the degeneracy between abundance and IMF variations, and may bring into doubt the use of the Wing-Ford band as an IMF index if used without other spectral information.